Behavioural design of gamification elements and exploration of player types in youth basketball training - Zeping Feng; Newman Lau; Mengxiao Zhu; Mengru Liu; Rehe Refati; Xiao Huang; Kun-pyo Lee (Smart Learning Environments, 2023)
Abstract In Mainland China, the sports training process of most players is highly homogenized, the convergence of which makes them ineffectively be identified with their individual and specific profile and difficult for them to play the sports according to their strengths and characteristics. Moreover, existing sports training software does not differentiate between player types to provide customized persona. Therefore, efficient and personalized methods need to be provided to guide players towards more autonomous sports training. Current research shows that gamification design in the process of sports training can transform players' unique conscious behaviors into habits, thus increasing their autonomy. However, the current gamification design in sports training is only based on uniform gamification elements and does not take into account the player's motivation and gamification experience, which is one of the main reasons for the homogenization of sports training. Therefore, this study aimed to identify factors that contribute to the design of gamification systems in the field of sports training, as well as to determine the relationship between players' gamification experiences during sport. It will help the researchers to explore in depth the possibilities of learning environments for youth basketball training with the development of gamified experiences. This design-driven study performed both offline and online questionnaire research (N = 198), which was analyzed with the method of a 7-point Likert scale as well as the assistance of SPSS, identified potential for the establishment of a framework for analysing preferences for gamification design elements in the context of basketball training for young players. Based on the results, this paper finds that there is a correlation between immersion and achievement in gamification experiences and proposes a framework for gamification system design in the field of sports training and offers insight that may enable the development of gamification designs that can motivate players.